Gastric perforation with foreign body granuloma formation caused by a short hair—a case report - Shen, Gang; Zhai, Yunpeng; Zhao, Huashan; Guo, Rui; Xu, Hongxiu; Huang, Sai; Zhang, Shisong (Frontiers in Pediatrics, 2025)
ObjectiveThis case report presents the diagnosis and treatment process of a rare case of gastric perforation caused by a short hair, leading to the formation of a foreign body granuloma in a child.Case ReportThe patient was a 3-year-old boy who was admitted to the hospital with persistent abdominal pain and fever for more than 20 days. Ultrasound and CT revealed a foreign body and inflammatory encapsulation in the abdominal cavity. Laparoscopic and open surgeries were performed, revealing a full-thickness gastric wall perforation approximately 2 mm in diameter on the greater curvature side of the stomach, which was in contact with the abscess and contained purulent fluid and short hair approximately 1.5 cm long. The intraoperative diagnosis was hair-induced gastric perforation, leading to intra-abdominal foreign body inflammatory granuloma. Granuloma excision, gastric perforation repair, and partial transverse colon resection were performed. Postoperative pathological results revealed a gastric perforation with surrounding acute and chronic inflammation, and the diagnosis was a reactive fibrous granulomatous lesion. The patient recovered well after surgery, and follow-up for one year revealed no significant abnormalities.ConclusionHair-induced gastric perforation leading to a foreign body granuloma formation is a rare disease. Imaging examinations play a key role in diagnosis, and surgical resection is the main treatment method.